2023
DOI: 10.3390/su15086975
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Spatial and Temporal Evolution of High-Quality Development in Nine Provinces of the Yellow River Basin

Abstract: High-quality development (HQD) is a positive initiative in China to promote sustainable development. Promoting HQD in the Yellow River Basin (YRB) is a major national strategy for China. The YRB is an important ecological barrier and economic zone in China, which comprises nine provinces, including Qinghai, Sichuan, Gansu, Ningxia, Inner Mongolia, Shaanxi, Shanxi, Henan and Shandong. The objective of this paper is to provide a comprehensive evaluation of the HQD of the nine provinces in the YRB. It clarifies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The estimated results are presented in Table 3. Columns (1) and (5) show the estimates of Eq (1) using OLS mixed regression without any additional control variables. When examining the growth of agricultural economic scale, it was found that financial marketization and its quadratic term have a significant impact at the 1% level.…”
Section: Analysis Of Benchmark Estimation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated results are presented in Table 3. Columns (1) and (5) show the estimates of Eq (1) using OLS mixed regression without any additional control variables. When examining the growth of agricultural economic scale, it was found that financial marketization and its quadratic term have a significant impact at the 1% level.…”
Section: Analysis Of Benchmark Estimation Resultsmentioning
confidence: 99%
“…However, China’s agricultural sector faces significant challenges, including high input costs, low efficiency, and serious land pollution, which have resulted in poor competitiveness when compared to the urban industrial economy [ 3 ]. The goal of High-quality development of agricultural economy (HQDAE) is to achieve sustainable development of the agricultural economy by improving total factor productivity and promoting agricultural modernization while ensuring national food security, promoting farmers’ income growth, and improving the ecological environment [ 4 , 5 ]. Therefore, finding a sustainable and efficient way to promote HQDAE and achieve the goal of sustainable development with zero hunger and poverty is an urgent issue that needs to be addressed.…”
Section: Introductionmentioning
confidence: 99%